Race over empire : racism and U.S. imperialism, 1865-1900 - Love, Eric Tyrone Lowery, 1965- (UNC Press law publications., 2004)
Generations of historians have maintained that in the last decade of the 19th century white-supremacist racial ideologies such as Anglo-Saxonism, social Darwinism, and the concept of the "white man's burden" drove American imperialist ventures in the nonwhite world. Eric T.L. Love contests this view and argues that racism had the opposite effect